PI3K Plays an Essential Role in Planarian Regeneration and Tissue Maintenance - Zheng, Hanxue; Liu, Hongbo; Xu, Qian; Wang, Wenjun; Li, Linfeng; Ye, Gang; Wen, Xiaomin; Chen, Fulin; Yu, Yuan (Frontiers in Cell and Developmental Biology, 2021)
Phosphatidylinositol 3-kinase (PI3K) signaling plays a central role in various biological processes, and its abnormality leads to a broad spectrum of human diseases, such as cancer, fibrosis, and immunological disorders. However, the mechanisms by which PI3K signaling regulates the behavior of stem cells during regeneration are poorly understood. Planarian flatworms possess abundant adult stem cells (called neoblasts) allowing them to develop remarkable regenerative capabilities, thus the animal represents an ideal model for studying stem cells and regenerative medicine in vivo. In this study, the spatiotemporal expression pattern of Djpi3k, a PI3K ortholog in the planarian Dugesia japonica, was investigated and suggests its potential role in wound response and tissue regeneration. A loss-of-function study was conducted using small molecules and RNA interference technique, providing evidence that PI3K signaling is required for blastema regrowth and cilia maintenance during planarian regeneration and homeostasis. Interestingly, the mitotic and apoptotic responses to amputation are substantially abated in PI3K inhibitor-treated regenerating animals, while knockdown of Djpi3k alleviates the mitotic response and postpones the peak of apoptotic cell death, which may contribute to the varying degrees of regenerative defects induced by the pharmacological and genetic approaches. These observations reveal novel roles for PI3K signaling in the regulation of the cellular responses to amputation during planarian regeneration and provide insights for investigating the disease-related genes in the regeneration-competent organism in vivo.